Zapisz sumy algebraiczne bez nawiasów. Zredukuj wyrazy podobne.

a) (6x - 7y) + (5x + 3y) - (5x + 4) =
b) -(3a) + (8 - 7a - 8b) - 20 =
c) (1,5m + 0,7n - 1) + (4m + n - 5) =
d) (a+b+c) - (4a - 2c + 7) + 25 =
Proszę o pomoc.
najlepiej z obliczeniami.

2

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-16T15:30:28+01:00
A) (6x - 7y) + (5x + 3y) - (5x + 4) =6x-7y+5x+3y-5x+4=6x-4y+4
b) -(3a) + (8 - 7a - 8b) - 20 =-3a+8-7a-8b-20=-10a-8b-14
c) (1,5m + 0,7n - 1) + (4m + n - 5) = 1,5m+0,7n-1+4m+n-5=5,5m+1,7n-6
d) (a+b+c) - (4a - 2c + 7) + 25 =a+b+c-4a+2c-7+25=-3a+b+3c+18
2010-02-16T15:33:25+01:00
A) (6x-7y)+(5x+3y)-(5x+4)=6x-7y+5x+3y-5x-4=6x-4y-4
b) -(3a)+(8-7a-8b)-20=-3a+8-7a-8b-20=-10a-8b-12
c) (1,5m+0,7n-1)+(4m+n-5)=1,5m+0,7n-1+4m+n-5=5,5m+1,7n-6
d) (a+b+c)-(4a-2c+7)+25=a+b+c-4a+2c-7+25=-3a+b+3c+18